PELATIHAN PARALEGAL BAGI MASYARAKAT PENDAMPING KORBAN KEKERASAN PEKERJA MIGRAN BERMASALAH DI DESA SUJUNG KECAMATAN TIRTAYASA - Ikomatussuniah, Ikomatussuniah; Ridwan, Ridwan; Solapari, Nuryati (Jurnal Pengabdian Dinamika, 2016)
Sujung village located in the district of Serang with 80% of the female population is migrant workers. Violence and abuse against the law happens to the workers. Counseling is necessary in order to provide education and legal knowledge for the workers. To that end, we was presented on the role of paralegals to support victims of violence against migrant workers in the Sujung village was given and paralegal training to support violence victims for migrant workers to improve public access to justice. The target audience were the migrant workers as many as 20 people, with the extension methods were lecturing, counseling and training. The material consists of a paralegal extension, recognize other forms of violence as a violation of human rights and access to legal aid for migrant workers in the Province of Banten by Legal Aid for the Poor Regulation 2014, Number 3.